The management of the patient with non-variceal upper gastrointestinal bleeding: from evidence to clinical practice - Maddalena Zippi; Mariella Frualdo; Luciano Mucci; Marta Zanon; Chiara Marzano; Claudio Cassieri; Paola Gnerre; Pietro Crispino (Italian Journal of Medicine, 2016)
A multidisciplinary group of 7 experts developed this update and expansion of the recommendations on the management of acute non-variceal upper gastrointestinal hemorrage (NVUGIH) from guidelines published from 2013. The Appraisal of Guidelines for Research and Evaluation (AGREE) process and independent ethics protocols were used. Sources of data included original and published systematic reviews. Recommendations emphasize early risk stratification, by using validated prognostic scales, and early endoscopy (within 24 h). Endoscopic hemostasis remains indicated for high-risk lesions, whereas data support attempts to dislodge clots with hemostatic, pharmacologic, or combination treatment of the underlying stigmata. Clips or thermocoagulation, alone or with epinephrine injection, are effective methods. Second-look endoscopy may be useful in selected highrisk patients, but is not routinely recommended. Intravenous high-dose proton pump inhibitors (PPI) therapy after successful endoscopic hemostasis decreases both rebleeding and mortality in patients with high-risk stigmata. Although selected patients can be discharged promptly after endoscopy, high-risk patients should be hospitalized for at least 72 h after endoscopic hemostasis. For patients with UGIH who require a nonsteroidal anti-inflammatory drug, a PPI is preferred to reduce the rebleeding. Patients with NVUGIH needing secondary cardiovascular prophylaxis should start receiving acetylsalicylic acid again as soon as cardiovascular risks outweigh gastrointestinal risks (usually within 7 days).